2005
DOI: 10.1093/jn/135.4.681
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Human Lipid Metabolism

Abstract: The existing work demonstrates that striking differences exist between men and women in lipid kinetics. These differences cannot be explained simply by the presence and action of sex hormones and are not always due to secondary, phenotypic traits that characterize men and women (e.g., body-composition, regional fat distribution). In fact, some of these secondary traits may even be the result of sexual dimorphism in metabolism, and being of female or male genotype also determines intermediary metabolism. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 69 publications
12
102
1
4
Order By: Relevance
“…The relatively large effect of fat mass on ASP in 21 This induces higher levels of fatty acids, and consequently, the effect of FFA on TG might mask the relatively small direct effect of fat mass on TG in the female model. The sexual dimorphism in effects of serum lipid levels on cIMT is likely to be affected by sex hormones as well.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively large effect of fat mass on ASP in 21 This induces higher levels of fatty acids, and consequently, the effect of FFA on TG might mask the relatively small direct effect of fat mass on TG in the female model. The sexual dimorphism in effects of serum lipid levels on cIMT is likely to be affected by sex hormones as well.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of sex-specific variation as a factor in the response of plasma lipids to variation in dietary macronutrients appears consistently in many studies, however [16,40,58]. We hypothesize that a genetic predisposition and sexual dimorphism may explain some of the variation in response of HDL-C levels to dietary carbohydrate intake [47,51].…”
Section: Introductionmentioning
confidence: 77%
“…Kataoka et al [32] study examining the relationship of APOE polymorphisms to plasma lipids in the original Strong Heart Study individuals (n = 4,410), reported sexspecific variation associated with APOE polymorphisms. Genotype was not significantly associated with HDL-C variation in males (ages [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64], however, in females, a significant trend for HDL-C levels was noted in all female subgroups studied: normal and diabetic, premenopausal and menopausal. HDL-C was higher in females carrying an e2 and lower in individuals carrying an e4 than for females with e3/3 genotypes.…”
Section: Genotype Effectsmentioning
confidence: 99%
See 2 more Smart Citations